Pembatalan Rencana Perkawinan Oleh Satu Pihak Yang Menimbulkan Kerugian - Jasmine, safira Yuvika; Dharsana, I Made Pria (Fakultas Syariah INSURI Ponorogo, 2023)
The annulment of a marriage plan can be filed as the basis for a tort lawsuit if there is an action by one of the parties that cause losses, both materially and immaterially. The party that causes the loss is given the obligation to make payments to the injured party. The research method in this writing uses Normative Juridical research or legal material collection techniques with library research. The legal sources used are primary, secondary, and tertiary legal sources. The qualitative research on unlawful acts of the cancellation of the marriage plan and the provision of compensation by the bride who cancelled plan. to compensate the prospective groom in actual compensation and compensation related to mental stress. The act of annulment of the marriage fulfils the elements of Article 1365 of the Civil Code, where the act is a tort contrary to written law and can also be unwritten law which violates the subjective rights of others so that the prospective bride violates the norms of decency and propriety in society and the losses incurred in real terms by the prospective groom for the preparation of the marriage must be replaced by the prospective bride who annuls the marriage.